Electronic Theses and Dissertations Workshop - Thomas, William Joseph; McConnell, Thomas J. (My University, 2014)
Presentation for graduating students who are required to deposit a thesis or dissertation. This presentation describes the deposit process using the Vireo ETD management system, the university's institutional repository, and common copyright issues.
Keywords: Electronic dissertations; Electronic theses